Barriers and facilitators of physical activity and sport participation among young transgender adults who are medically transitioning. Issue 2 (3rd April 2017) - Jones, Bethany Alice; Arcelus, Jon; Bouman, Walter Pierre; Haycraft, Emma
ABSTRACT: Background : Transgender people (those who feel incongruence between the gender they were assigned at birth and their gender identity) engage in lower levels of physical activity compared to cisgender (non-transgender) people. Several factors have been shown to affect physical activity engagement in the cisgender population; however, the physical activity experiences of young transgender adults have not been explored. It is therefore the aim of the current study to understand what factors are associated with physical activity and sport engagement in young transgender adults who are medically transitioning. Method : Semi-structured interviews were conducted with 14 young transgender adults (18–36 years) who had initiated their medical transition at a transgender health service in the United Kingdom. The data were analyzed using thematic analysis. Results : Two main themes were identified: (1) barriers and (2) facilitators to physical activity and sport. Overall, the young transgender adults were insufficiently active due to inadequate changing facilities, body dissatisfaction, fears surrounding "passing" and not being accepted by others. At the same time, participants were motivated to engage in physical activity to increase their body satisfaction and gender congruence. However, participants felt there was a lack of safe and comfortable spaces to engage in physical activity and sport. Conclusion : Young transgender adults who are medically transitioning experience several barriers to physical activity and sport, despite being motivated to be physically active. Initiatives to facilitate young transgender adults' ability to put their motivations into practice (i.e. to be more physically active) are needed.